DIGITAL TRANSFORMATION IN MARKETING: A MULTI-DIMENSIONAL ANALYSIS OF STRATEGIES, CHALLENGES, AND OPPORTUNITIES - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Digital transformation has significantly changed the marketing landscape, forcing companies to adapt quickly to the changing business environment. The review in this research uses literature. The results show that digital transformation has opened up new opportunities for companies to improve their marketing efficiency, personalization, and reach. However, challenges such as data security, customer privacy, and the digital skills gap have also emerged as important issues to overcome. With that said, digital transformation in marketing offers great potential for innovation and business growth, but also requires a careful and strategic approach.